Jakarta – Berlin Collaboration in Implementing Jakarta Smart City and Achieving SDGs - Mujiono, Rayhan Krisna; Haqqi, Halifa; Anugrah, Alma Fuji (Journal of Paradiplomacy and City Networks, 2025)
The Jakarta Provincial Government has officially partnered with Berlin in developing a smart city through the Smart Change program, supported by the European Union (EU). This collaboration aims to strengthen Jakarta’s smart city initiative, which has been under development since 2014, to achieve the Sustainable Development Goals (SDGs). Using a descriptive qualitative research method, this study comprehensively examined the Jakarta Smart City (JSC) program and its alignment with the SDGs. The findings unveiled that JSC has made progress in implementing the smart city initiative and contributing to SDG achievements. However, further optimization in regulatory implementation, funding mechanisms, and public participation were required to ensure more effective outcomes. Enhancing these elements would help Jakarta’s smart city initiative achieve its goals more effectively and substantially.